Laser ablation inductively coupled plasma mass spectrometry imaging of metals in experimental and clinical Wilson's disease - Boaru-Szatkowski, Sorina Georgiana; Merle, Uta; Flechtenmacher, Christa; Stremmel, Wolfgang (Journal of cellular and molecular medicine, 2014)
Wilson's disease is an autosomal recessive disorder in which the liver does not properly release copper into bile, resulting in prominent copper accumulation in various tissues. Affected patients suffer from hepatic disorders and severe neurological defects. Experimental studies in mutant mice in which the copper-transporting ATPase gene (Atp7b) is disrupted revealed a drastic, time-dependent accumulation of hepatic copper that is accompanied by formation of regenerative nodes resembling cirrhosis. Therefore, these mice represent an excellent exploratory model for Wilson's disease. However, the precise time course in hepatic copper accumulation and its impact on other trace metals within the liver is yet poorly understood. We have recently established novel laser ablation inductively coupled plasma mass spectrometry protocols allowing quantitative metal imaging in human and murine liver tissue with high sensitivity, spatial resolution, specificity and quantification ability. By use of these techniques, we here aimed to comparatively analyse hepatic metal content in wild-type and Atp7b deficient mice during ageing. We demonstrate that the age-dependent accumulation of hepatic copper is strictly associated with a simultaneous increase in iron and zinc, while the intrahepatic concentration and distribution of other metals or metalloids is not affected. The same findings were obtained in well-defined human liver samples that were obtained from patients suffering from Wilson's disease. We conclude that in Wilson's disease the imbalances of hepatic copper during ageing are closely correlated with alterations in intrahepatic iron and zinc content.
Gesehen am 28.07.2017